M(m-4)-(m+3)(m-4)=(m-4)(m-m-3)=-3(m-4)=3(4-m)
при любом целом значении m данное выражение обязательно делится на 3
x+3y=5
-3·x+y+2·z=10 ВЕРНО
-x+y+z=6
I 1 3 0 I
Δ = I -3 1 2 I = 1-0-6+0-2+9=2
I -1 1 1 I
I 5 3 0 I
Δₓ₁ = I 10 1 2 I = 5+0+36-0-10-30=1 x1=x=Δₓ₁ /Δ =1/2
I 6 1 1 I
I 1 5 3 I
Δₓ₂ = I -3 10 2 I = 10-0-10-0-12+15=3 x2=y=Δₓ₂ /Δ =3/2
I -1 6 1 I
I 1 3 5 I
Δₓ₃= I -3 1 10 I = 6-15-30+5-10+54=10 x3=x=Δₓ₃ /Δ =10/2=5
I-1 1 6 I
проверка
(1./2)+3(3/2)=5
-3·(1/2)+(3/2)+2·5=10 ВЕРНО
-(1/2)+3/2+5=6
ОТВЕТ X=1/2; Y=3/2;Z=5
Ответ:
42*23+17*18+24*17=6*7*23+17*6*3+6*4*17=6*(7*23+17*3+4*17)=6*(7*23+17*(3+4))=
=6*(7*23+17*7)=6*(7*(23+17)=6*7*40=42*40=1680
Пошаговое объяснение: